Detection of mitochondrial dysfunction in vitro by laser‐induced autofluorescence. Issue 11 (23rd July 2019) - Raghushaker, Chandavalli R.; Chandra, Subhash; Chakrabarty, Sanjiban; Kabekkodu, Shama P.; Satyamoorthy, Kapaettu; Mahato, Krishna K.
Abstract: Mitochondrion plays a significant role in a variety of biological functions. Because of their diverse character and location in the cellular systems, mitochondria commonly get exposed to various extrinsic and intrinsic cellular stresses. The present study reports a novel approach to detection of mitochondrial dysfunction based on tryptophan autofluorescence of its proteins in mouse liver, using laser‐induced fluorescence (LIF) as a tool. Mitochondria, isolated from the mouse liver, were initially tested for purity and integrity using lactate dehydrogenase and succinate dehydrogenase (SDH) assays. Mitochondrial stress was induced by treating the isolated mitochondria with heavy metals at 10 and 0.01 mM for sodium arsenite and mercuric chloride, respectively. Upon treatment with the heavy metal, tryptophan autofluorescence quenching was recorded at 281 nm excitation. The functional integrity of the mitochondria treated with heavy metals was evaluated by measuring SDH and cytochrome c oxidase activities at various concentrations of mitochondria, which showed impaired activity as compared to control upto a concentration of 6.25 μg. A significant shift was also observed in the autofluorescence of proteins upto the level below 1 μg, suggesting their conformational change and hence altered structural integrity of mitochondria. Circular dichroism spectroscopy data of the mitochondrial proteins treated with heavy metals further validates their conformational change as compared to untreated control. The present study clearly shows that the LIF can be a novel detection tool to detect altered structural integrity of cellular mitochondria upon stress, and it also possesses the potentiality to combine with other interdisciplinary modalities. Abstract : The present study reports a novel approach to detection of mitochondrial dysfunction based on tryptophan autofluorescence of its proteins in mouse liver model, using laser‐induced fluorescence (LIF) as a tool. The study clearly shows that LIF can be a tool to detect altered structural integrity of cellular mitochondria upon stress, and it also possesses the potential to combine with other interdisciplinary modalities.